Living indigenous archives - Thorpe, Kirsten, author.
1 online resource (208 pages)
Keywords: Living Indigenous Archives invites readers to consider new pathways for developing and sustaining archival landscapes that are embedded with respect for Indigenous worldviews and cultural flows of knowledge.Drawing on First Nations experiences in Australia, the book considers the need to reframe archives in order to rebalance power and restore dignity to the Aboriginal and Torres Strait Islander people captured in the archives. Contributing to research on the contested nature of archives and the need for archival decolonisation, the book examines whether current, dominant approaches to archiving and managing Aboriginal and Torres Strait Islander knowledges support Indigenous people's wellbeing and recognize Indigenous sovereignty in an archival context. Drawing on autoethnographical research and a series of yarning sessions with First Nations people, the book shares a number of case studies that discuss themes related to Indigenous archiving. These include: community engagement approaches to facilitate reciprocal relationships and counter-storytelling; archival reparations; enacting protocols to support archives' spiritual and emotional care; and the support for Indigenous language revitalization in archives.Living Indigenous Archives highlights the need for Indigenous reclamation of archives and the dismantling of colonial archiving models that are harmful to Indigenous people's wellbeing. The book's theoretical and practical underpinnings will be relevant to academics and students working in archival studies, as well as those engaged in the study of library and information science, Indigenous peoples and history.